An introductory note on Quasicrystals - Sharma, B G (Recent Research in Science and Technology, 2012)
This paper presents a brief introduction of the research on a new class of materials called quasicrystals. Starting from history of its development, paper discusses about its growth mechanism and its applications. Contents of the paper are based on various sources available and no originality of the article is claimed by the author.